2014
DOI: 10.7150/thno.8343
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Breast Tumor Initiating Cells Using the Extra Domain-B of Fibronectin Targeting Nanoparticles

Abstract: The identification of breast tumor initiating cells (BTICs) is important for the diagnosis and therapy of breast cancers. This study was undertaken to evaluate whether the extra domain-B of fibronectin (EDB-FN) could be used as a new biomarker for BTICs and whether EDB-FN targeting superparamagnetic iron oxide nanoparticles (SPIONs) could be used as a magnetic resonance imaging (MRI) contrast agent for BTIC imaging in vitro and in vivo. BTICs (NDY-1) exhibited high EDB-FN expression, whereas non-BTICs (MCF-7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…APT EDB -TCL-SPIO nanoparticles showed significant accumulation in breast tumor initiating cells, NDY-1, with specific overexpression of EDB-FN. In contrast, APT EDB -TCL-SPIO, could not bind to non-breast tumor initiating cells, such MCF-7 cells, which had low EDB-FN expression 103 .…”
Section: Targeting Fibronectin For Cancer Imagingmentioning
confidence: 82%
See 2 more Smart Citations
“…APT EDB -TCL-SPIO nanoparticles showed significant accumulation in breast tumor initiating cells, NDY-1, with specific overexpression of EDB-FN. In contrast, APT EDB -TCL-SPIO, could not bind to non-breast tumor initiating cells, such MCF-7 cells, which had low EDB-FN expression 103 .…”
Section: Targeting Fibronectin For Cancer Imagingmentioning
confidence: 82%
“…It has been shown that CREKA-SPIO could induce additional plasma clotting in tumor, producing binding sites for more nanoparticles. This clotting-based amplification greatly enhanced tumor imaging 98, 99, 103 . Preparation of the APT EDB labeled SPION nanoparticles is depicted in Figure 6.…”
Section: Targeting Fibronectin For Cancer Imagingmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have already demonstrated the potential of antibody-mediated EDB-FN targeting (using L19, BC-1) for angiogenesis, inflammation, and cancer stem cell therapy (Mariani et al, 1997, Tijink et al, 2009). EDB-FN-specific peptides, such as ZD2 and APT EDB , are advantageous for oncogenic ECM targeting, by virtue of their small size, low immunogenicity, and high tissue penetration ability (Han et al, 2015, Sun et al, 2014, Zahnd et al, 2010). The specificity and superior binding of the ZD2 probe for EDB-FN has direct translational implications.…”
Section: Discussionmentioning
confidence: 99%
“…This differential expression of EDB-FN was exploited for differentially diagnosing invasive prostate and breast cancer tumors from the non-invasive xenografts using EDB-FN-targeted MRI contrast agents (Ayat et al, 2018, Han et al, 2017a, Han et al, 2017b). Other independent groups have also used EDB-FN as a molecular target for targeted imaging and therapeutic delivery for various types of cancer (Sun et al, 2014, Ye et al, 2017, Han et al, 2019).…”
Section: Introductionmentioning
confidence: 99%